A transactional runtime system for the Cell/BE architecture - Baldassin, Alexandro José [UNESP]; Goldstein, Felipe; Azevedo, Rodolfo (Academic Press Inc. Elsevier B.V., 2012)
Single-core architectures have hit the end of the road and industry and academia are currently exploiting new multicore design alternatives. In special, heterogeneous multicore architectures have attracted a lot of attention but developing applications for such architectures is not an easy task due to the lack of appropriate tools and programming models. We present the design of a runtime system for the Cell/BE architecture that works with memory transactions. Transactional programs are automatically instrumented by the compiler, shortening development time and avoiding synchronization mistakes usually present in lock-based approaches (such as deadlock). Experimental results conducted with a prototype implementation and the STAMP benchmark show good scalability for applications with moderate to low contention levels, and whose transactions are not too small. For those cases in which a small performance loss is admissible, we believe that the ease of programming provided by transactions greatly pays off. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Multiprocessors; Parallel programming; Transactional memory